การใช้สัญลักษณ์ท่าทางเพื่อควบคุมการทำงาน ของกูเกิลแมปส์โดยใช้กล้องความลึกสามมิติคิเนกท์ - ภพธร ลี้ตระกูล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The objective of this independent study on the topic of “Gestures Control of Google Maps Using Kinect 3D Depth Camera” was to develop an intuitive 3D interface using a Kinect 3D depth camera sensor on personal computer for google maps applications control. For this purpose we performed body segmentation based on the depth map of the user and tracked the body movement across background. Based on the tracking information we detected and recognized various gestures. For each of the gesture recognized we then performed mouse actions to control a google maps application that applied with Kinect 3D depth camera. The results were satisfactory and the efficiency of the gestures were recognized to a good degree of accuracy in all 3 interesting subjects, the speed of processing, the ease of gestures control, and the appropriate selection of gestures. Finally, the overall results were consistent with the objective of the study.